FILSAFAT MANUSIA DALAM ILMU PENGETAHUAN SYARIAH DI LINGKUNGAN SOSIAL KEAGAMAAN INDONESIA - Fahrany, Sofia; Mamang, Damrah; Huwaida, Hasna'; Sirojuddin, Sirojuddin; Yasin, Rahman (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2025)
Human philosophy is a servant of Allah SWT who has the task of preaching to command goodness and avoid the prohibitions of Allah as stated in the At-Tahrim Letter verse 6